Perioperative complications of complex abdominal wall reconstruction with biologic mesh: A pooled retrospective cohort analysis of 220 patients from two academic centers. (February 2020) - Latifi, Rifat; Samson, David J.; Gogna, Shekhar; Joseph, Bellal A.
Abstract: Background: Perioperative outcomes in patients who undergo complex abdominal wall reconstruction (CAWR) may be associated with severe complications, mainly when these procedures are done urgently or emergently. This study aims to identify perioperative predictors of outcomes after CAWR with biologic mesh (BM). Materials and methods: In a retrospective study, perioperative complications (length of hospital stay, ventilator support, surgical site infection, need for wound VAC, reoperation, total complications, and mortality), were analyzed in all patients who underwent open CAWR with BM over six years in two academic centers. Furthermore, we examined the effect of cardiac disease, BMI, diabetes, COPD, case mixed index, hernia size, wound classification, mesh technique, the setting of surgery, on perioperative complications. Multivariable linear and logistic regression analyses were performed. Results: There were 220 patients: 134 patients from center A and 86 patients from center W Mean age was 54.9 ± 14.8 years, 47.7% were females, 33.8% of the patients had BMI ≥30 kg/m2 and median hospital length of stay was 7 days. Center W patients had increased need for mechanical ventilation (10.5% vs. 3%, p = 0.02) and higher need for wound VAC (19.8% vs. 6.7%, p = 0.003). On multivariable linear regression, independent patient predictors of increased hospital length of stay (HLO) were: urgent/emergent surgery (β 6.93, 95% CI 1.65–12.22, p = 0.01), cardiac disease (β 7.84, 95% CI 1.23–14.46, p = 0.02) and epigastric defect (β 13.68, 95% CI 0.29–27.06, p = 0.045). Addition-ally, urgent/emergent setting (OR 3.06, 95% CI 1.69–5.55, p < 0.001) and cardiac disease (OR 2.15, 95% CI 1.03–4.50, p = 0.042) were independently associated with increased odds for perioperative complications. Conclusions: Perioperative complications of patients undergoing CAWR are considerable and depend on defect complexities, the setting of surgery, comorbidities, wound classification, procedural factors, and case-mix index. Prospective studies on perioperative complications are needed. Highlights: This study identifies the outcome predictors for CAWR with biologic mesh. We have included large number of patients from two different centers and the rigorous statistical methods were employed. This study will be a meaningful contribution to the literature pertaining to outcomes after CAWR with biological mesh.